The Mind of a Poet The Prelude, Commentary - Havens, Raymond Dexter (Johns Hopkins University Press, 2020)
This book seeks to study the mind of a poet, specifically by picking William Wordsworth as a case study. The reason for signaling out Wordsworth as the person in whom to study the mind of a poet is that The Prelude reveals with unusual fullness a mind that is fundamentally poetic. Even its peculiarities, its numerous limitations, and its unusual emphases are in the main those of a poet. Besides, poetry-not, as with many other writers, religious or social problems, humanitarianism, science, politics, economics, metaphysics, or literary criticism-was the chief concern of his creative years. Further, the sheer amount of verse, criticism, letters, and journals Wordsworth produced makes him an excellent choice for a study of this kind.